ANALISIS DAYA SAING LEMBAGA KURSUS DAN PELATIHAN (LKP) GLOBAL LINGUA BREBES DI KABUPATEN BREBES - Medi Tri Purwanto (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2017)
ABSTRAK This study aims to determine the strengths, weaknesses, opportunities, and threats in the Global Lingua Brebes LKP and to find out what factors influence the customer to choose a course at the Global LKP Lingua Brebes. Based on internal and external analysis of the institution along with the cartesius diagram it can be found that the main strategy of the Lingua Brebes Global LKP is the Growth Strategy, where the Global Lingua Brebes LKP can develop its market share and educational programs by developing the capabilities of employees and educators. Based on the SWOT matrix, we can conclude some developments through consideration of the internal and external factors of the institution that can be useful for the progress of the Lingua Brebes Global LKP. With SWOT analysis, educational institutions can see the strengths, weaknesses, opportunities and threats that can create promotional and marketing strategies right in order to be able to compete with similar institutions. Keywords: SWOT, Competitiveness